Regulation of Mouse Small Heat Shock Protein αb-Crystallin Gene by Aryl Hydrocarbon Receptor - Liu, Shuang (Public Library of Science, 2011)
The stress-inducible small heat shock protein (shsp)/αB-crystallin gene is expressed highly in the lens and moderately in other tissues. Here we provide evidence that it is a target gene of the aryl hydrocarbon receptor (AhR) transcription factor. A sequence (−329/−323, CATGCGA) similar to the consensus xenobiotic responsive element (XRE), called here XRE-like, is present in the αBE2 region of αB-crystallin enhancer and can bind AhR in vitro and in vivo. αB-crystallin protein levels were reduced in retina, lens, cornea, heart, skeletal muscle and cultured muscle fibroblasts of AhR(−/−) mice; αB-crystallin mRNA levels were reduced in the eye, heart and skeletal muscle of AhR(−/−) mice. Increased AhR stimulated αB-crystallin expression in transfection experiments conducted in conjunction with the aryl hydrocarbon receptor nuclear translocator (ARNT) and decreased AhR reduced αB-crystallin expression. AhR effect on aB-crystallin promoter activity was cell-dependent in transfection experiments. AhR up-regulated αB-crystallin promoter activity in transfected HeLa, NIH3T3 and COS-7 cells in the absence of exogenously added ligand (TCDD), but had no effect on the αB-crystallin promoter in C(2)C(12), CV-1 or Hepa-1 cells with or without TCDD. TCDD enhanced AhR-stimulated αB-crystallin promoter activity in transfected αTN4 cells. AhR could bind to an XRE-like site in the αB-crystallin enhancer in vitro and in vivo. Finally, site-specific mutagenesis experiments showed that the XRE-like motif was necessary for both basal and maximal AhR-induction of αB-crystallin promoter activity. Our data strongly suggest that AhR is a regulator of αB-crystallin gene expression and provide new avenues of research for the mechanism of tissue-specific αB-crystallin gene regulation under normal and physiologically stressed conditions.